2020
DOI: 10.1177/1076029619900544
|View full text |Cite
|
Sign up to set email alerts
|

Blood Group Types O and Non-O Are Associated With Coronary Collateral Circulation Development

Abstract: Blood group types are associated with coronary artery disease. However, data are scarce about the impact of blood group types on coronary collateral circulation. In this study, we aimed to investigate the relationship between the blood group types and coronary collateral circulation. Two hundred and twelve patients who underwent coronary angiography in our department and had a stenosis of ≥ 90% in at least one major epicardial vessel were included in our study. Collateral degree was graded according to Rentrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A study conducted by Celebi et al evaluated the association between blood group types and the development of coronary collateral circulation in 212 patients with CAD and reported that poor collateral development is associated with non-O blood group type 17 . However, like our findings, a study by Rasmi et al in an Iranian population also observed no association between the number of diseased vessels and ABO distribution of blood group 18 .…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Celebi et al evaluated the association between blood group types and the development of coronary collateral circulation in 212 patients with CAD and reported that poor collateral development is associated with non-O blood group type 17 . However, like our findings, a study by Rasmi et al in an Iranian population also observed no association between the number of diseased vessels and ABO distribution of blood group 18 .…”
Section: Resultsmentioning
confidence: 99%
“…That's why the present study is original and valuable with respect to data and context. However, there are studies to explain the relation between CHD and ABO blood groups (15,16,17). and we know that coronary heart disease has a similar etiology with carotid artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…It was emphasized in one study that the individuals in the Non-O blood group had more severe coronary artery stenosis and that the Non-O blood group could pose a risk for CHD (9). Besides, coronary heart disease was found to be less common among people with an O blood group (15). Compared to the O blood group, A, B, or AB blood groups have an increased risk of coronary heart disease by 5%, 11%, and 23%, respectively (18).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies have indicated that individuals with non-O blood groups demonstrate an increased risk for several thromboembolic diseases, including ischemic heart disease, pulmonary thromboembolism (PE), and deep vein thrombosis [8][9] , as well as familial hypercholesterolemia [10] . Recently, a trial aimed to investigate the relationship between blood group type and coronary collateral circulation also demonstrated that O blood group predicts good coronary collateral development among patients with coronary artery disease [11] . Similarly, patients with non-O blood group types have a higher risk for development of high-grade atrioventricular block (HAVB) compared with O blood group patients [12] , and blood group A is associated with the risk of myocardial infarction (MI) [13] .…”
Section: Abo Blood Group and Cardiovascu-lar Diseasesmentioning
confidence: 99%